2005
DOI: 10.1152/japplphysiol.00156.2005
|View full text |Cite
|
Sign up to set email alerts
|

Acute hypoosmolality attenuates the suppression of cutaneous vasodilation with increased exercise intensity

Abstract: We examined the hypothesis that elevation of the body core temperature threshold for forearm skin vasodilation (TH(FVC)) with increased exercise intensity is partially caused by concomitantly increased plasma osmolality (P(osmol)). Eight young male subjects, wearing a body suit perfused with warm water to maintain the mean skin temperature at 34 +/- 1 degree C (ranges), performed 20-min cycle-ergometer exercise at 30% peak aerobic power (VO2(peak)) under isoosmotic conditions (C), and at 65% VO2(peak) under is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 29 publications
(37 reference statements)
0
16
0
Order By: Relevance
“…20 and 30% Ex) was not enough for a statistical analysis because of the small increase in core temperature during the exercise. Mitono et al (2005) have reported that the T es threshold for forearm vasodilation measured using venous occlusion plethysmography was signiWcantly higher during 60% VO 2peak than 30% VO 2peak under isoosmotic conditions. Thus it is possible that plethysmography can sensitively detect the eVect of exercise on the T es threshold, but the blood Xow obtained from plethysmography includes blood Xow in both muscle and skin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 and 30% Ex) was not enough for a statistical analysis because of the small increase in core temperature during the exercise. Mitono et al (2005) have reported that the T es threshold for forearm vasodilation measured using venous occlusion plethysmography was signiWcantly higher during 60% VO 2peak than 30% VO 2peak under isoosmotic conditions. Thus it is possible that plethysmography can sensitively detect the eVect of exercise on the T es threshold, but the blood Xow obtained from plethysmography includes blood Xow in both muscle and skin.…”
Section: Discussionmentioning
confidence: 99%
“…Cutaneous vasomotor response during the exercise is inXuenced by factors other than core body and skin temperatures. Central motor command, changes in mechano-receptor and metabo-receptor activities in muscles, changes in osmoreceptor activity, and some others have been proposed as nonthermal factors (Christensen et al 1942;Johnson 1986;Johnson and Park 1982;Kondo 1999;Mitono et al 2005). It is considered, therefore, that nonthermal factors occurring with exercise increased in an intensity-dependent manner adrenergic vasoconstrictor activity in the glabrous skin.…”
Section: Discussionmentioning
confidence: 99%
“…Changes of the extracellular osmotic pressure are often found in some pathologic conditions, such as diabetes mellitus, uremia, dehydration after exercise, heat shock, fatal burns, and inflammation sites in various tissues including the cornea (1)(2)(3)(4). It has been shown that persistent hyperosmotic stress can induce DNA damage, cell cycle arrest, and apoptosis (5,6).…”
mentioning
confidence: 99%
“…The increased T es thresholds at a given increase in P osm during exercise were identical to those during resting passive heat stress [23]. Mitono et al [24] supported this evidence by indicating that when the increase in P osm during exercise was attenuated by hypotonic saline infusion prior to exercise, the delayed onset of cutaneous vasodilation in response to increased T es during exercise was normalized. It has been suggested that the response of the thermoregulatory center was attenuated by plasma hyperosmolality via osmoreceptors.…”
Section: Thermoregulation In Warm and Hot Conditionsmentioning
confidence: 79%